Organizational commitment or community participation? Identifying the stronger driver of village SDGS achievement in Indonesia - Handayani, Bestari Dwi; Dedi, Priantana Riha; Hidayah, Raudhatul; Suryanto, Edy (Asian Development Policy Review, 2025)
The achievement of Village Sustainable Development Goals (SDGs) is a national priority in Indonesia; however, challenges such as corruption and limited transparency in village fund management continue to impede progress. This study examines the influence of community participation and organizational commitment as contingency variables on Village SDG achievement in Poncowarno District, Central Java. Using purposive sampling, 44 respondents participated in the study, with data collected through questionnaires and analyzed using multiple regression and moderation regression analysis (MRA) in SPSS. The results reveal that accountability in village financial management has a significant positive effect on Village SDG achievement (β = 0.744; sig. = 0.000). Community participation shows a negative but insignificant effect (β = -0.012; sig. = 0.526), while organizational commitment significantly strengthens the relationship (β = 0.030; sig. = 0.006). The model’s R Square of 0.725 indicates that 72.5% of the variation in Village SDG achievement is explained by the independent and moderating variables. These findings underscore the vital role of organizational commitment in fostering Village SDG outcomes. Strengthening commitment through capacity-building, leadership development, and institutional incentives is crucial for improving governance and accelerating sustainable development in Indonesian villages.